Severe hypoxemia induced by prolonged expiration and reduced frequency breathing during submaximal swimming - Toubekis, A. G.; Beidaris, N.; Botonis, P. G.; Koskolou, M. (Journal of Sports Sciences, 2017)
The purpose of this study was to examine the metabolic responses during submaximal swimming with self-selected normal breathing (N) and prolonged expiration along with reduced frequency breathing (RB). Ten male swimmers (age: 23.1 ± 2.2 years; VO2max: 47.3 ± 7.2 ml /kg·min) performed 75-, 100-, 175-, 200-, 275-, 300-, 375- and 400-m trials with N and RB at intensity corresponding to 90% of the critical speed. In RB condition, all trials longer than 75 m were interspersed with 25 m of self-selected N in regular intervals. In RB, oxygen saturation during recovery was decreased compared to starting values after 75, 100, 175, 275 and 375 m (78-91%, P < 0.05), while it remained unchanged after all trials in N condition (98 ± 2%, P > 0.05). Lactate concentration was higher in RB than in N after 400 m (4.3 ± 1.5 vs. 3.3 ± 1.7 mmol/l, P < 0.05). During recovery after the 375-m trial, partial pressure of carbon dioxide was increased and pH was decreased in RB compared to N condition. Prolonged expiration along with RB provokes severe hypoxemia during the recovery period after swimming, which is restored with self-selected N during submaximal swimming.